Determinants of early initiation of breastfeeding in The Gambia: a population-based study using the 2019-2020 demographic and health survey data - Muhammed L Darboe; Angeline Jeyakumar; Salma M. A. Mansour; Shahanara Valawalkar (BMC, 2023)
Abstract Background Early initiation of breastfeeding within the first hour of life prevents neonatal and infant mortality. Sustainable Development Goals (SDGs) Target 3.2 aims to reduce neonatal mortality and under 5 mortality globally. The decline in the early initiation of breastfeeding in The Gambia coincides with deviations from the SDGs, due to poor indicators of child survival. Our work studied the determinants of early initiation of breastfeeding in The Gambia. Methods We used the 2019-2020 Gambia Demographic Health Survey (GDHS) conducted across all regions of the country. Since our population of interest was children born two years preceding the study, we only included children less than 24 months of age, living with an eligible respondent. Thus, a weighted sample of 5691 mother-child pairs was applied in the analysis. We reported summary statistics of individuals' sociodemographic, obstetrics and antenatal, household, and community-level factors. A logistic regression model was used to determine associations between early initiation of breastfeeding and covariates. Results The prevalence of early initiation of breastfeeding was 64.3% (n = 3659). Mothers who had secondary education or higher educational level had higher odds of early initiation of breastfeeding (AOR 1.22; 95% CI 1.07, 1.40). Regions with rural population notably Lower and Central and Upper River Region had lower odds of early initiation of breastfeeding [Mansakonko (AOR 0.37; 95% CI 0.26, 0.15), Kerewan (AOR 0.26; 95% CI 0.19, 0.36), Kuntaur (AOR 0.39; 95% CI 0.28, 0.54), Janjanbureh (AOR 0.48; 95% CI 0.35, 0.66) and Basse (AOR 0.64; 95%CI 0.49, 0.85)]. Also, women in the high quintile of the wealth index were more likely to initiate breastfeeding early (AOR 1.29; 95% CI 1.06, 1.57). Four or more antenatal care visits did not increase early initiation of breastfeeding. Conclusions The results of the analyses demand affirmative action to improve maternal education, reduce poverty and inequality and empower rural communities in The Gambia. The IYCF component in antenatal care needs to be strengthened. Programs and policies on IYCF must resonate to address determinants of timely breastfeeding initiation to chart progress towards the SDG.